The englishization of higher education in Europe - Wilkinson, Robert, 1949-; Gabriëls, René (Amsterdam University Press, 2021)
The introduction of English as a medium of instruction (EMI) has changed higher education enormously in many European countries. This development is increasingly encapsulated under the term Englishization, that is, the increasing dispersion of English as a means of communication in non-Anglophone contexts. Englishization is not undisputed. Nor is it uniform. In this volume, authors from 15 European countries present analyses from a range of perspectives coalescing around four core concerns: the quality of education, cultural identity, inequality of opportunities and questions of justice and democracy.